A scale for measuring perceived bureaucratic readiness for smart cities in Indonesia - Arif Budy Pratama; Satria Aji Imawan (Public Administration and Policy, 2019)
Purpose – The purpose of this paper is to develop and validate a scale for measuring perceived bureaucratic readiness for smart city initiatives. Design/methodology/approach – The present study employs a mixed method approach to achieve its research objectives. An exploratory study, consisting of literature review and qualitative interviews with key informants, was conducted to develop an initial instrument for measuring bureaucratic readiness. An online survey of 40 civil servants involved in smart city programmes in the Yogyakarta City government was then administered to test the instrument’s validity and reliability. Findings – Perceived bureaucratic readiness can be measured through four dimensions: commitment of the upper echelons, legal support, information technology resources and governance. Research limitations/implications – The proposed scale provides an alternative instrument for measuring perceived bureaucratic readiness for smart city initiatives. However, as data were only derived from one city government, they are relatively small in scope. Future research can be conducted for generalisation by replicating this study in other cities, thereby measuring its effectiveness in other contexts and settings. Practical implications – This study not only provides a better understanding of bureaucratic readiness for smart city initiatives, but also proposes an assessment tool as a practical means of assessing bureaucratic readiness. The quantification of readiness is beneficial to putting smart city programmes into practice, as it allows smart city managers to assess the internal bureaucracy’s level of readiness. It also allows managers to mitigate and further policy agendas and thereby improve the bureaucracy’s support for smart city programmes. Originality/value – Literature sometimes underestimates the role of bureaucracy in smart city implementation while overly stressing stakeholders, vendors and technology. This paper attempts to contribute to smart city research by reaching beyond the technological perspective and focusing on local government bureaucracy. None of the extant literature provides a scale for measuring bureaucratic readiness. The study thus proposes a systematic way to develop a means of measuring perceived bureaucratic readiness for smart city programmes.